Inoculation Methods and Conidial Densities of Fusarium oxysporum f.sp. cubense in Abaca - RULLY DYAH PURWATI; NURUL HIDAYAH; SUDJINDRO SUDJINDRO; SUDARSONO2? SUDARSONO2? (Bogor Agricultural University, Indonesia, 2008)
Abaca (Musa textilis Nee) is an important industrial crop. Its cultivation in Indonesia is, however, hampered by the wilt (Panama disease) caused by Fusarium oxysporum f.sp. cubense (Foc) infections. Developing Foc resistance abaca lines require availability of established and reliable screening methods for resistance against Foc. The objectives of this study were to evaluate the (i) effectiveness of Foc inoculation methods, (ii) extent of Foc conidial densities – for causing the wilt in abaca, and (iii) responses of ten abaca cultivars against Foc infection. Results of this study showed that the method of inoculation by wounding abaca roots followed submerging the wounded plant in suspension of Foc conidia (106 conidia/ml) for 2 hours before planting was the most effective method for causing the wilt. Among ten abaca cultivars tested, none was resistant to Foc infection. Based on the calculation of disease intensity, nine abaca cultivars were identified as very susceptible, where as one cultivar was susceptible to Foc infection. Key words: Fusarium wilt, panama disease, disease response, screening method, Musa textilis